2021
DOI: 10.3390/ijms221910556
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic and Proteomic Alterations Induced by Even and Odd Medium-Chain Fatty Acids on Fibroblasts of Long-Chain Fatty Acid Oxidation Disorders

Abstract: Medium-chain fatty acids (mc-FAs) are currently applied in the treatment of long-chain fatty acid oxidation disorders (lc-FAOD) characterized by impaired β-oxidation. Here, we performed lipidomic and proteomic analysis in fibroblasts from patients with very long-chain acyl-CoA dehydrogenase (VLCADD) and long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHADD) deficiencies after incubation with heptanoate (C7) and octanoate (C8). Defects of β-oxidation induced striking proteomic alterations, whereas the effect of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 71 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…In LCHADD/MTPD they may, therefore, share the co-responsibility for the specific development of retinopathy and peripheral neuropathy. This hypothesis is supported by the fact that the incubation of fibroblasts of LCHADD patients with medium chain fatty acids, especially heptanoate, avoids the biosynthesis and accumulation of long-chain hydroxy acylcarnitines, contributes to the restoration of the sphingolipid content and profile and makes this similar to those observed in the fibroblasts of healthy controls [8]. In accordance to this hypothesis, Francis et al 2013 reported an improvement in oligodendrocyte survival and myelination in a mouse model of Canavan Disease [70].…”
Section: Sphingomyelins and Ceramides: New Co-player For Neurodegener...mentioning
confidence: 88%
See 3 more Smart Citations
“…In LCHADD/MTPD they may, therefore, share the co-responsibility for the specific development of retinopathy and peripheral neuropathy. This hypothesis is supported by the fact that the incubation of fibroblasts of LCHADD patients with medium chain fatty acids, especially heptanoate, avoids the biosynthesis and accumulation of long-chain hydroxy acylcarnitines, contributes to the restoration of the sphingolipid content and profile and makes this similar to those observed in the fibroblasts of healthy controls [8]. In accordance to this hypothesis, Francis et al 2013 reported an improvement in oligodendrocyte survival and myelination in a mouse model of Canavan Disease [70].…”
Section: Sphingomyelins and Ceramides: New Co-player For Neurodegener...mentioning
confidence: 88%
“…It is therefore conceivable that sequence variants affecting MTP enzyme activity result in an altered cardiolipin profile [7]. At the same time, an aberrant cardiolipin profile reduces mitochondrial fusion and fission processes [18][19][20] and leads to the destabilization of mitochondrial supercomplexes and the dysregulation of energy metabolism [7,8]. Analysis in human fibroblasts has highlighted that the LCHADD induces cardiolipin remodeling with a subsequent profile alteration and incorporation of the non-metabolized C16 fatty acids into cardiolipin species [7].…”
Section: Mitochondrial Trifunctional Protein (Mtp) and Cardiolipinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the abnormal PC/PE ratio, the increased levels of plasmalogens and lyso-PL support the theory of inflammatory processes in lc-FAOD. Recently, Alatibi et al showed that the application of saturated medium-chain FA (especially C7) leads to an altered composition of membrane lipids in patient’s fibroblasts, especially observed in LCHADD fibroblasts [ 133 , 139 ]. In addition, treatment with MCFA seemed to be particularly beneficial in fibroblast cell lines of FAOD patients by supporting mitochondrial metabolism and by enabling restoration of the SL metabolic flux, and reducing the protein expression known to be involved in neurodegenerative diseases.…”
Section: Lipid*omic*s In Rare Diseasesmentioning
confidence: 99%